2021
DOI: 10.13057/biodiv/d221238
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, coverage, distribution and ecosystem services of seagrass in three small islands of northern Papua, Indonesia: Liki Island, Meossu Island and Befondi Island

Abstract: Nugraha AH, Tasabaramo IA, Hernawan UE, Rahmawati S, Putra RD, Darus RF. 2021. Diversity, coverage, distribution and ecosystem services of seagrass in three small islands of northern Papua, Indonesia: Liki Island, Meossu Island and Befondi Island. Biodiversitas 22: 5544-5549. Papua waters are one of the hot spot areas with high marine biodiversity in the world. Yet, the less accessible location and varying geographical conditions become the significant constraints of biodiversity study in this region, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Seagrasses are shallow coastal flowering marine plants that can be formed as extensive meadows or beds (Short et al 2007;Nugraha et al 2021) which play an important role as they provide ecosystem services (ES) to the coastal marine environment (Duarte et al 2013;Nordlund et al 2018). Decreasing of seagrass area can affect the ecosystem surrounding areas such as loss of nursery ground for fishes, reduction the detritus producer, lack of coastline protection, increase in coastal erosion, decrease in water clarity improvement, changes in nutrient regulation and carbon sequestration (Costanza et al 2014;Nordlund et al 2016;Boudouresque et al 2016;Unsworth et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Seagrasses are shallow coastal flowering marine plants that can be formed as extensive meadows or beds (Short et al 2007;Nugraha et al 2021) which play an important role as they provide ecosystem services (ES) to the coastal marine environment (Duarte et al 2013;Nordlund et al 2018). Decreasing of seagrass area can affect the ecosystem surrounding areas such as loss of nursery ground for fishes, reduction the detritus producer, lack of coastline protection, increase in coastal erosion, decrease in water clarity improvement, changes in nutrient regulation and carbon sequestration (Costanza et al 2014;Nordlund et al 2016;Boudouresque et al 2016;Unsworth et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ambo-Rappe (2022) indicated the successful seagrass restoration using seeds in Spermonde Island, Indonesia, was determined by the area's exposure to wave actions. Other research in northern Papua (Nugraha et al, 2021) and Talaud Islands (Kawaroe et al, 2016) suggested the correlation between low coverage of seagrass meadows in the study areas with high wave exposure. However, most seagrass studies in Indonesia did not provide proper observations of the hydrodynamics, causing the lack of evidence and scientific explanations underlying the phenomena.…”
Section: Figurementioning
confidence: 60%
“…Seagrass life is influenced by environmental conditions such as substrate, temperature, salinity, nutrients, brightness, and current speed (Fitrian et al 2017). Seagrass plays a significant role in fisheries (Nugraha et al 2021). Ecologically, seagrass provides habitat, spawning grounds, and shelter for fish and invertebrates (Unsworth et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ex Solms) Asch., and Thalassodendron ciliatum (Forssk.) Hartog (Sjafrie et al 2018;Kurniawan et al 2020;Nugraha et al 2021). The area of seagrass beds in Indonesia in 2017 was around 293,464 ha, with moderate conditions (Sjafrie et al 2018;Hernawan et al 2021).…”
Section: Introductionmentioning
confidence: 99%